Inter-laboratory evaluation of SNP-based forensic identification by massively parallel sequencing using the Ion PGM™. (July 2015) - Eduardoff, M.; Santos, C.; de la Puente, M.; Gross, T.E.; Fondevila, M.; Strobl, C.; Sobrino, B.; Ballard, D.; Schneider, P.M.; Carracedo, Á.; Lareu, M.V.; Parson, W.; et al.
Graphical abstract: Highlights: Evaluation of the HID-Ion AmpliSeq™ Identity Panel v2.2 was performed between three laboratories. Levels of sequence coverage, sensitivity, ability to detect mixed DNA and genotyping precision were assessed. High coverage levels were obtained for the majority of the 169 SNPs studied for input DNA levels as low as 25–100 pg and the overall genotyping concordance rate was 99.8%. Mixed source DNAs can be detected but further optimisation of the analysis parameter settings is needed. Certain component SNPs underperform so they should be excluded from the panel or their data discounted during the analysis. The HID-Ion AmpliSeq™ Identity Panel and Ion PGM™ system provide a sensitive and accurate genotyping assay highly applicable to forensic analysis. Abstract: Next generation sequencing (NGS) offers the opportunity to analyse forensic DNA samples and obtain massively parallel coverage of targeted short sequences with the variants they carry. We evaluated the levels of sequence coverage, genotyping precision, sensitivity and mixed DNA patterns of a prototype version of the first commercial forensic NGS kit: the HID-Ion AmpliSeq™ Identity Panel with 169-markers designed for the Ion PGM™ system. Evaluations were made between three laboratories following closely matched Ion PGM™ protocols and a simple validation framework of shared DNA controls. The sequence coverage obtained was extensive for the bulk of SNPs targeted by the HID-Ion AmpliSeq™ Identity Panel. Sensitivity studies showed 90–95% of SNP genotypes could be obtained from 25 to 100 pg of input DNA. Genotyping concordance tests included Coriell cell-line control DNA analyses checked against whole-genome sequencing data from 1000 Genomes and Complete Genomics, indicating a very high concordance rate of 99.8%. Discordant genotypes detected in rs1979255, rs1004357, rs938283, rs2032597 and rs2399332 indicate these loci should be excluded from the panel. Therefore, the HID-Ion AmpliSeq™ Identity Panel and Ion PGM™ system provide a sensitive and accurate forensic SNP genotyping assay. However, low-level DNA produced much more varied sequence coverage and in forensic use the Ion PGM™ system will require careful calibration of the total samples loaded per chip to preserve the genotyping reliability seen in routine forensic DNA. Furthermore, assessments of mixed DNA indicate the user's control of sequence analysis parameter settings is necessary to ensure mixtures are detected robustly. Given the sensitivity of Ion PGM™, this aspect of forensic genotyping requires further optimisation before massively parallel sequencing is applied to routine casework.